Motives and Rivalry of Superpower Countries: The United States and China in Rohingya Humanitarian Crisis - Achmad Ismail (Jurnal Hubungan Internasional, 2018)
This article argues that behind the response to the Rohing crisis problem, there are economic and political motives as soft forces penetrated by both countries as a form of influence rivalry. Some previous article examine the rivalry between the two countries in various regions with a military focus and so on. Qualitative research methods with case study approaches and data techniques with interviews and literature studies become this article. The conclusion that this happened in the United States and the issue of the Rohingya issue was a major issue, but behind that, there were other motives that were the main objectives of the two countries.